The Urgency of Strengthening Social Sciences Education in Elementary Schools in Forming Good Citizens - Elisya Laili Rahmadani; Fitri Ningsih; Fiqril Khaikal; Gebby Fortuna; Herlin Juniarti (MANDALIKA : Journal of Social Science, 2023)
Social studies education is a branch of social science that has a significant influence in forming good citizens. Therefore, improving social studies teaching in elementary schools is very important to pay attention to. The aim of this research is to find out how important social studies teaching is in elementary schools, namely: first, learning social studies in elementary schools as strengthening character education. second, the urgency of learning social studies as an instrument for instilling students' character values of tolerance. Third, social studies learning problems. Fourth, the urgency of learning social studies in an effort to strengthen Indonesian students' understanding of democracy. Fifth, the role of social studies learning in strengthening the character of students in upper elementary schools. The method used in this research is a literature review study to provide the need for improving social studies teaching in elementary schools so that students can become better citizens. Literature analysis is carried out by reading and citing quotations from several scientific works related to the research topic. Information obtained from the literature is then researched and combined to answer the questions asked. The references used in this writing refer to relevant sources, such as academic texts published by related parties, research results, and other written sources. To strengthen the finding that the social studies program in elementary schools has a strong urgency in forming good citizens, various data were used by identifying individual information, such as journals, books and other documents. The results of implementing several strategies show that strengthening social studies education in elementary schools can improve well.